2017
DOI: 10.1177/0972150917721798
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Human Resource Expenses on Business Value: Focus on Welfare and Training Expenses in Listed Korean Stock Markets

Abstract: This article investigates whether investment in education and training and welfare expenses can help promote corporate value. If such expenditures are found to affect enterprise value, this evidence should lead to a revision of the current accounting treatment of education and training and welfare expenses in the Republic of Korea. The empirical results show that the book value of equity, education and training expenses and welfare costs has positive relationships with enterprise value, whereas accounting earn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
5
2
Order By: Relevance
“…Based on empirical evidence, HR investment does not have significant influence on firm value. The result of this study is not the same as prior research (García-Zambrano et al, 2018;Holland, 2017;Joh & Jung, 2016;Kwon, 2011Kwon, , 2017) that shows the significant and positive influence of HR investment on firm value.…”
Section: Methodscontrasting
confidence: 97%
See 2 more Smart Citations
“…Based on empirical evidence, HR investment does not have significant influence on firm value. The result of this study is not the same as prior research (García-Zambrano et al, 2018;Holland, 2017;Joh & Jung, 2016;Kwon, 2011Kwon, , 2017) that shows the significant and positive influence of HR investment on firm value.…”
Section: Methodscontrasting
confidence: 97%
“…HRI coefficient value of 0,0000254 shows that HRI has a positive This study provides new findings related to the relationship between HR investment and firm value. Prior studies found evidence that companies try to increase their value by increasing the HR quality (García-Zambrano et al, 2018;Holland, 2017;Joh & Jung, 2016;Kwon, 2011Kwon, , 2017. According to Human Capital Theory by Becker (1975), high quality HR will increase a firm's productivity that leads to an escalation in a firm's performance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kwon [14] presents the results of empirical research that book value of equity, expense education and training, and welfare costs have a positive relationship with enterprise value, while accounting earnings have a significant negative impact on enterprise value. Ho et al [11] suggested that intensive investment in advertising contributed positively to the performance of one year with shares of non-invoicing companies.…”
Section: Introductionmentioning
confidence: 99%
“…Also in the paper Marketing and Management of Innovations, 2020, Issue 3 321 http://mmi.fem.sumdu.edu.ua/en the main determinants of the human resource accounting were defined: rationality and multidisciplinary problemsolving approaches which characterise management science was applied to human resource accounting and economic and social factors of the 1960s. The newest article (Kwon, 2019) investigates how investment in developing human capital can help promote corporate value. The empirical results of the article show that the book value of equity, education and training expenses and welfare costs has positive relationships with enterprise value.…”
mentioning
confidence: 99%